Development and Research on the Music (Singing) Course for the Elderly: A Case Study of The Seniors University of Taizhou - Ji, Xingyu; Wang, Qiran; Ren, Zihan; Hu, Yi; Wang, Jiye (Pacific International Journal, 2024)
With China’s rapidly growing elderly population, music education for seniors has become essential in enhancing their spiritual well-being and overall quality of life. The Taizhou Municipal Government actively supports national policies aimed at building a high-quality elderly care system, and this study explores a singing course offered at The Seniors University of Taizhou. Through the theme of “singing for the motherland,” this course encourages elderly participants to connect with their memories of the past, foster teamwork, and engage in meaningful social interaction. The course incorporates historical and theoretical elements of music, using diversified teaching methods to stimulate learning interest. This study contributes valuable insights into the impact of music education on elderly individuals’ emotional, social, and mental health, aiming to guide further research on music courses in the elderly care sector.